Pengentasan Kemiskinan Berbasis Jasa Ekosistem - Zairin Zairin (Universitas Prof. Dr. Hazairin, S.H, 2017)
Poverty is a matter of concern to the world, especially in developing countries like Indonesia. This is evidenced by the adoption of the Millennium Development Goals (MDGs) by the United Nations, which is one of its objectives is to eradicate poverty and hunger. There are many things that governments can do about reducing poverty, because the government basically has the ability to access and manage natural resources, such as forests. Providing compensation for environmental services in the form of land management rights to poor farmers is believed to be able to reduce poverty and income distribution. In addition, other forms of increasing public incomes can also be made by strengthening roles in managing natural resources sustainably. Government policies to support the development of